KUALITAS MADRASAH DAN PROFESIONALISME GURU (UNDANG-UNDANG 14 TAHUN 2005) - Febriyanti Febriyanti (El-Idare, 2016)
Madrasah as an Islamic institution that has existed since before the independence of the Republic of Indonesia gets tough challenges due to the demands of ever-changing society; increasingly demanding quality madrasah. The shift value is driven by the demands of globalization make LMU madrasah that combines public and the science of religion even got a chance in preparing the generation is ready and able to face the challenges of his time. With the moral capital strong religious, science and modern technology into the necessities of life, then the madrasah as education-based society will remain an option for parents, not only to send their children go to madrasah, but also his participation for the implementation of quality education, to encourage the planting base Basics competitive advantage.